2020
DOI: 10.1111/peps.12432
|View full text |Cite
|
Sign up to set email alerts
|

What are the career implications of “seeing eye to eye”? Examining the role of leader–member exchange (LMX) agreement on employability and career outcomes

Abstract: Are there career benefits to leaders and followers agreeing about the quality of their leader-member exchange (LMX) relationship? Is LMX disagreement always detrimental for a follower's career? Can the examination of LMX agreementThis is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 102 publications
(172 reference statements)
0
18
0
Order By: Relevance
“…There is also evidence for implications of LMX on employees' work and their performance as well as career-related outcomes [10,82,83]. For example, LMX quality was shown to play an important role in employees' employability [10].…”
Section: Leader-member Exchange As a Moderator Of The Relationship Be...mentioning
confidence: 99%
See 3 more Smart Citations
“…There is also evidence for implications of LMX on employees' work and their performance as well as career-related outcomes [10,82,83]. For example, LMX quality was shown to play an important role in employees' employability [10].…”
Section: Leader-member Exchange As a Moderator Of The Relationship Be...mentioning
confidence: 99%
“…There is also evidence for implications of LMX on employees' work and their performance as well as career-related outcomes [10,82,83]. For example, LMX quality was shown to play an important role in employees' employability [10]. Similarly, others found that LMX positively moderated the relationship between job-related activities (i.e., learning) and employability [83].…”
Section: Leader-member Exchange As a Moderator Of The Relationship Be...mentioning
confidence: 99%
See 2 more Smart Citations
“…Vocational development has been an important topic for organizational research already for decades (Katzell, 1948), as the development of human resources plays a major role in ensuring a sustainable competitive advantage (Aguinis & Bradley, 2015). In this context, the development of executives is of special interest for many reasons, including its impact on business unit performance (Song et al, 2020), the wide range of influences on development (Deng et al, 2021; Epitropaki et al, 2021; McClean et al, 2021), and the decisive role it plays in mastering organizational challenges (Meffert & Wagner, 1992). Yet the development of executives remains a struggle (Lacerenza et al, 2017; Schied, 2001; Powell & Yalcin, 2010), especially given the changes due to the current pandemic (Caligiuri et al, 2020), and the struggle is likely to increase as many companies are forced to transform and adapt to changes faster than ever before (Arora & Suri, 2020).…”
mentioning
confidence: 99%